A Nonselective Cation Channel in Adult Alveolar Epithelial Cells - Beverley A Orser; Jeffrey D Edelson (Canadian Respiratory Journal)
OBJECTIVE: Efficient gas exchange across the alveolar membrane requires a dry air space. At birth, active Na+ transport provides the major driving force for absorption of fetal lung liquid, and during adult life, similar transport mechanisms balance fluid exchange across the alveolarcapillary membrane. A cation channel, previously identified in fetal alveolar epithe lium, may represent one of several pathways which regulate apical-basal transepithelial Na+ flux. The purpose of this study was to determine if cation channels are also present in adult alveolar epithelial cells.